Clinical characteristics and outcome of 318 families with familial monoclonal gammopathy: A multicenter Intergroupe Francophone du Myélome study. Issue 2 (1st January 2023) - Dumontet, Charles; Demangel, Delphine; Galia, Perrine; Karlin, Lionel; Roche, Laurent; Fauvernier, Mathieu; Golfier, Camille; Laude, Marie‐Charlotte; Leleu, Xavier; Rodon, Philippe; Roussel, Murielle; Azaïs, Isabelle; et al.
Abstract: Familial forms of monoclonal gammopathy, defined as multiple myeloma (MM) or Monoclonal Gammopathy of Undetermined Significance (MGUS), are relatively infrequent and most series reported in the literature describe a limited number of families. MM rarely occurs in a familial context. MGUS is observed much more commonly, which can in some cases evolve toward full‐blown MM. Although recurrent cytogenetic abnormalities have been described in tumor cells of sporadic cases of MM, the pathogenesis of familial MM remains largely unexplained. In order to identify genetic factors predisposing to familial monoclonal gammopathy, the Intergroupe Francophone du Myélome identified 318 families with at least two confirmed cases of monoclonal gammopathy. There were 169 families with parent/child pairs and 164 families with cases in at least two siblings, compatible with an autosomal transmission. These familial cases were compared with sporadic cases who were matched for age at diagnosis, sex and immunoglobulin isotype, with 10 sporadic cases for each familial case. The gender distribution, age and immunoglobulin subtypes of familial cases were unremarkable in comparison to sporadic cases. With a median follow‐up of 7.4 years after diagnosis, the percentage of MGUS cases having evolved to MM was 3%. The median overall survival of the 148 familial MM cases was longer than that of matched sporadic cases, with projected values of 7.6 and 16.1 years in patients older and younger than 65 years, respectively. These data suggest that familial cases of monoclonal gammopathy are similar to sporadic cases in terms of clinical presentation and carry a better prognosis.